Corrective feedback and students' uptake in adult ESL communicative classroom - Lau, Aileen Ek Ling (Universiti Malaysia Sarawak (UNIMAS), 2008)
This study was designed to examine the patterns of en-or treatment sequence in adult ESL communicative classrooms in a tertiary institution. The study investigated the types of corrective feedback used by the instructors and their relationship to students' uptake of feedback and immediate repair of error. A case study was conducted to observe the classroom interaction of 20 classes of students with the average of 30 students per class. From the audio taped recording of the 20 two-hour classroom interaction sessions, 96 incidents comprising of en-ors, con-ective feedback and learner uptake were identified and coded according to Lyster and Ranta's (1997) corrective discourse model. The results included the frequency and distribution of the three ditferent language errors, six different feedback types used by the instructors, and nine different types of students' uptake following each feedback type. The tindings revealed a clear preference for instructors to notice and respond to grammatical and phonological errors. Results indicated an overwhelming tendency for instructors to use recasts to elicit students' response to the feedback, which mostly were repetition and incorporation of the correct form. The study also revealed that recasts were inetfective in encouraging student-generated repairs in spite of the latter's high frequency of use. Consequently, frequency of learners' uptake in tenns of immediate student-generated repair of en-or was low in this study. Other feedback types such as metalinguistic feedback and clarification requests led to student-generated repairs more successfully and allowed students to negotiate the form as the correct form of target language was not provided to students. Generally, the findings have practical applications in the context of ESL communicative classrooms in relation to en-or treatment sequence.